HUBUNGAN SLEEP HYGIENE DENGAN KUALITAS TIDUR MAHASISWA FAKULTAS ILMU KOMUNIKASI UNIVERSITAS BHAYANGKARA JAKARTA RAYA 2021 - Hidayati Bunga, Dinda Nur Fajri; Asyhari, Tias Tri; Indrawati, Lina (STIKes Medistra Indonesia, 2022)
Adolescents and young adults have been identified as a population at high risk of experiencing sleep problems and daytime sleepiness by The National Institute of Health (NIH). The student group is a group that has a fairly solid activity. In the morning most of the students got up early to prepare for class. The quality of student sleep can be influenced by several factors, one of which can be caused by the application of poor sleep hygiene. Sleep Hygiene consists of the sleeping environment, habits and behaviors that are often done before bed. Students can improve their sleep quality well if they can perform sleep hygiene activities properly. To explain the relationship between sleep hygiene and sleep quality in students of the Faculty of Communication Sciences, Bhayangkara University, Greater Jakarta. This research method is a quantitative design using a cross sectional analytic research design. The population of this research is active students of Bhayangkara University, Jakarta Raya University, using simple random sampling technique. Based on the results of statistical analysis using the chi square test, the p value of 0.005 0.05 was obtained. This shows that H0 is rejected. There is a Relationship between Sleep Hygiene and Sleep Quality for Students of the Faculty of Communication Sciences, Bhayangkara University, Jakarta Raya 2021.